Phylogenetic study and taxonomic update of Chondrina (Gastropoda, Pulmonata, Chondrinidae) in the Cantabrian Mountain region (Iberian Peninsula). Issue 3 (19th April 2021) - Somoza-Valdeolmillos, Eder; Vázquez-Sanz, Julen; Gómez-Moliner, Benjamín J.; Caro, Amaia; Madeira, María J.
Abstract : This study revises the taxonomy and species limits of Chondrina taxa living in the Cantabrian mountain region of N Spain, based mainly on molecular data but supplemented with morphological data. One new species C. cantabroccidentalis Somoza-Valdeolmillos & Vázquez-Sanz sp. nov. is here described as the species of the genus living in the western Cantabrian Mountains. In addition, we propose new subspecies divisions for C. kobelti, namely C. k. kobelti and C. k. ordunensis, living to the west and east of Picos de Europa, respectively. Both subspecies are well distinguished according to their DNA profiles and morphology, and several hybrid populations have been identified in the contact zone. Finally, the species limits of C. cliendentata and C. kobeltoides are redefined and phylogenetic relationships among all these taxa and their closest relatives analysed by multilocus DNA sequencing. http://zoobank.org/urn:lsid:zoobank.org:pub:0E2652FE-39C2-4A70-B8D5-5F9E1114AAED